Evaluating the potential health risk of organocisahlorine pesticides in selected protein foods from Abeokuta southwestern Nigeria. Issue 1 (1st January 2020) - Taiwo, Adewale Matthew; Talabi, Oluseye Philip; Akintola, Abdulahi Akingbolahan; Babatunde, Ezekiel Tosin; Olanrewaju, Moarufat Olajumoke; Adegbaju, Boluwatife Helen; Odebo, Samson Lekan; Bello, Aishat Ajoke; Matti, Oluwatosin Fatimah; Adesanya, Adeniran Anthony; Ahmad, Sakinat Mojisola
ABSTRACT: This study evaluated the potential health risk of OCPs in selected protein foods. A total of 66 food samples were collected from selected areas in Abeokuta, southwestern Nigeria. Food samples were analyzed for OCPs using the standard method. OCP data were analysed for descriptive and inferential statistics. Health risk assessment was conducted for non-carcinogenic {Hazard Quotient (HQ), Hazard Index (HI) and Cancer Risk (CR)}. The ΣOCP concentration was observed highest in pork (42.20 ± 33.33 mg kg −1 ) of which methoxychlor and dieldrin represented 63 and 28%, respectively. The HIs of OCPs in protein foods were generally greater than 1.0 indicating adverse effects. The ΣCR data showed carcinogenic effects in protein foods with values greater than the acceptable limit of 1.0 × 10 −4 .